Quantitative evaluation of electrical conductivity inside stress corrosion crack with electromagnetic NDE methods. (14th September 2020) - Cai, Wenlu; Jomdecha, Cherdpong; Zhao, Yingsong; Wang, Li; Xie, Shejuan; Chen, Zhenmao
Abstract : This paper presents a comparison of studies on the local distributed electrical conductivity in stress corrosion crack (SCC) from signals of eddy current testing (ECT) and direct current potential drop (DCPD) aiming to improve SCC sizing accuracy when using electromagnetic non-destructive testing (NDT) methods. Experimental setups of ECT and DCPD were established, respectively, to collect measurement signals due to artificial SCCs in a plate of austenitic stainless steel. The local conductivity in the SCC region was reconstructed from the feature parameters extracted from the measured ECT and DCPD signals through inverse analyses. The inversion strategies for ECT and DCPD, each including an efficient forward simulation and an optimization scheme, were introduced from the viewpoint of conductivity reconstruction. Inversion results obtained from the measured ECT and DCPD signals showed the consistent trend which proved the validity of the predicted electrical conductivity indirectly. It is clarified that the electrical conductivity in a SCC is relatively high at the crack tip area and may become as high as 17% of that of the base material. These results provide a good reference to enhance the sizing accuracy of SCC with an electromagnetic NDT method such as ECT by updating the conductive crack model based on the results of this work. This article is part of the theme issue 'Advanced electromagnetic non-destructive evaluation and smart monitoring'.